Tetralogy of Fallot With Right Aortic Arch and Retro-Aortic Innominate Vein - Lim, Zhia N.; Chew, Bryan J. W.; Yong, Sanfui; Corno, Antonio F. (Frontiers in Pediatrics, 2018)
Right aortic arch (RAA) and retro-aortic innominate vein are rare vascular anomalies. Diagnosis of these anatomical variations can be achieved using fetal echocardiography, post-natal echocardiography and computed tomography scan. RAA can form a vascular ring when associated with other vascular anomalies which may compress the trachea and/or esophagus. On the other hand, the existence of retro-aortic innominate vein can influence the clinical decision-making and surgical strategy. We report a rare occurrence of both RAA and retro-aortic innominate vein in a three-month old girl with a prenatal diagnosis of tetralogy of Fallot and include details of her presentation and successful management.